ANALISIS PENGARUH PENERAPAN ETIKA DAN PENINGKATAN PROFESIONALISME AUDITOR TERHADAP KUALITAS AUDITOR INTERNAL - Sarsiti - (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2015)
The purpose of this research was to understand the effect of the application of the rules of ethics, professionalism increase of internal auditor to audit quality in the Internal Auditor Industry at Surakarta Municipality. The research object is the Internal Auditor in the industry at Surakarta Municipality. The research population of 120 respondents, and the sample 60. The data was collected by questionnaire. Research analysis with multiple linear regression. The results of the t test analysis can be seen that the p - value (0,001 < 0,05), means that Ho is rejected and accepted Ha, meaning there are influence perception Applying Ethics Rules (X1), increased professionalism of internal auditors to audit quality of the Internal Auditor Industry at Surakarta Municipality. The application of ethical rules and professionalism increased internal auditors simultaneous having influence an significant to audit quality in the Internal Auditor Industry at Surakarta Municipality. This can be seen from the value of Fcount > Ftable (106,700 > 3,15). So can be meaning that independent variable variation such as of application of the rules of ethics, (X1) and professionalism increase (X2) have contribution effect to internal auditor quality to industry at Surakarta Municipality (Y) as big as 72,2% while left as big as 27,8% the effect by other factor such as experience, morality education and auditor independention.Keywords: Application of the rules of ethics, increased professionalism of internal auditors, audit quality